Sustainable development in India : issues and approaches - Indian Economic Association. Annual Conference 2010 : Punjab University); Thakur, Anil Kumar; Dalīpa Kumāra, 1963- (New Delhi : Published on behalf of the Indian Economic Association by Regal Publications, 2013)
Papers presented at the 93rd Annual Conference of the Indian Economic Association, held at Punjab University during 27-29 December 2010.
pt. 1. Sustainable development and environmental issues -- pt. 2. Sustainable development and environmental managements.
Includes bibliographical references and index.
Keywords: Sustainable development -- India -- Congresses; Economic development -- India -- Congresses